IMPLEMENTASI BUKU ADVENTURE NARRATIVES BASED ON JOYFUL LEARNING TERHADAP PENINGKATAN KETERAMPILAN MEMBACA SISWA KELAS III SDN ANTASAN BESAR 1 BANJARMASIN - Rina Pasaribu, Duma; Normalasarie (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Reading skills are foundational competencies for elementary school students. However, the literacy level of third-grade students at SDN Antasan Besar 1 Banjarmasin was relatively low due to the lack of interactive media and learning motivation. As an innovative solution, a Joyful Learning approach was applied using the Adventure Narratives book based on local Kalimantan wisdom. This study aims to determine whether the implementation of the book can improve reading skills overall and describe the improvement after its application. This quantitative research used a Pre-Experimental One-Group Pretest-Posttest Design with a total sample of 25 third-grade students. Reading comprehension data, covering explicit information, detailed information, and main ideas, were collected through 20 valid and reliable multiple-choice test items. Data analysis techniques included the Shapiro-Wilk normality test, Paired Sample t-Test, and N-Gain Score test using IBM SPSS Statistics. The results showed that: First, the implementation of the Adventure Narratives book significantly improved students' reading skills overall, as proven by the rejection of H0 in the Paired Sample t-Test (sig. 0.000 < 0.05) with a Mean Difference of 25 points. Second, the description of students' reading skills improvement showed a very positive and even distribution, where the average score jumped from 65.80 (pretest) to 93.60 (posttest). This is supported by an average N-Gain Score of 0.82 (high category). This study concludes that adventure-based joyful media is highly effective in improving elementary students' literacy.